An adaptive force and posture control strategy for automated wiring terminal assembly. Issue 8 (3rd August 2022) - Li, Jing-Rong; Wang, Zhi-Jie; Wang, Yi-Yu; Wang, Qing-Hui
ABSTRACT: Mainstream industrial practice of assembling different flexible wires into the connector is manual due to different specifications of terminals and flexible wire assembly requirements. Therefore, the efficiency of the production and the quality of the assembly rely heavily on the knowledge and experiences of human workers. To reduce the labor cost and possible errors, this paper presents an adaptive force and posture control strategy for automated wiring terminal assembly (WTA). The contact force states during the search phase and insertion phase are first analyzed and then modeled. With the force analysis, fuzzy-PID controllers are applied for translational and angular adjustment during the assembly process. To validate the control strategy proposed, a prototype system is set up by integrating a force/torque (F/T) sensor and cameras on an industrial robot. And two kinds of industrial wires with four types of different wire terminals are tested with comparative studies. The results have shown that the proposed control strategy is able to conduct automatic insertion with different flexible wires successfully with reliable force feedback.